TRANSLATION OF ANIMATION AND FILM TEXTS: CHALLENGES, STRATEGIES, AND BEST PRACTICES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The translation of animation and film texts, including subtitles, dialogues, and scripts, plays a crucial role in making audiovisual content accessible to global audiences. This article explores the topic using the IMRAD format, providing a comprehensive overview of the introduction to the field, methodological approaches, key results from existing studies, and a discussion of implications. Drawing from linguistic, cultural, and technical perspectives, it highlights the unique challenges posed by multimedia elements such as timing, humor, and visual cues. The findings underscore the need for adaptive strategies to preserve meaning and entertainment value across languages.